(untitled) (Entrepreneurship Journal for Finance and Business, 2025)
The purpose of this research is to clarify the importance of the barcode in monitoring processes, as it plays a significant role in the circulation of goods between the producer and the consumer. It also aims to highlight the benefits and significance of barcodes across various stages of the production process, including identifying the components of the manufactured product and reinforcing the role of barcodes within business organizations. Barcodes help accurately track products within warehouses, thereby facilitating daily or periodic inventory processes and minimizing human errors. Thanks to barcodes, inventory levels can be effectively monitored, allowing the organization to plan ahead to avoid stock shortages or overstocking. Moreover, barcodes play a key role in protecting the rights of both the initial and final consumer.